Trends in anthropogenic CO2 in water masses of the Subtropical North Atlantic Ocean. (February 2015) - Guallart, Elisa F.; Schuster, Ute; Fajar, Noelia M.; Legge, Oliver; Brown, Peter; Pelejero, Carles; Messias, Marie-Jose; Calvo, Eva; Watson, Andrew; Ríos, Aida F.; Pérez, Fiz F.
Highlights: The greatest Cant enrichment (∼1 μmol kg −1 yr −1 ) is found in the uppermost layer. Zonal variability in the decadal Cant storage rates becomes significant below 1000 m. The Labrador Sea Water contributes remarkably to the deeper Cant enrichment. Cant has been absorbed more intensively in the western side of the Subtropical Gyre. Cant penetration is comparable to measurements in Atlantic fixed time series stations. Abstract: The variability in the storage of the oceanic anthropogenic CO2 (Cant ) on decadal timescales is evaluated within the main water masses of the Subtropical North Atlantic along 24.5°N. Inorganic carbon measurements on five cruises of the A05 section are used to assess the changes in Cant between 1992 and 2011, using four methods (ΔC ∗, TrOCA, φ CT 0, TTD). We find good agreement between the Cant distribution and storage obtained using chlorofluorocarbons and CO2 measurements in both the vertical and horizontal scales. Cant distribution shows higher concentrations and greater decadal storage rates in the upper layers with both values decreasing with depth. The greatest enrichment is obserbed in the central water masses, with their upper limb showing a mean annual accumulation of about 1 μmol kg −1 yr −1 and the lower limb showing, on average, half that value. We detect zonal gradients in the accumulation of Cant . This finding is less clear in the upper waters, where greater variability exists between methods. In accordance with data from time series stations, greater accumulation of Cant is observed in the upper waters of the western basin of the North Atlantic Subtropical Gyre. In intermediate and deep layers, the zonal gradient in the storage of Cant is more robust between methods. The much lower mean storage rates found along the section (<0.25 μmol kg −1 yr −1 ) become more obvious when longitudinal differences in the Cant accumulation are considered. In particular, west of 70°W the ventilation by the Labrador Sea Water creates a noticeable accumulation rate up to ∼0.5 μmol kg −1 yr −1 between 1000 and 2500 dbar. If a Transient Stationary State of the Cant distributions is considered, significant bi-decadal trends in the Cant storage rates in the deepest North Atlantic waters are detected, in agreement with recent estimations.